Assessing Effectiveness of anaerobic threshold and respiratory compensation point on fat and carbohydrate oxidations during exercise in sedentary males: Anaerobic Threshold and Substrate Oxidation - Ugras, Seda; Algul, Sermin; Ozcelik, Oguz (Progress in Nutrition, 2021)
Study Objectives: Anaerobic threshold (AT) and respiratory compensation point (RCP) are two important metabolic set points. We aimed to determine effects of exercise intensity at AT and RCP on the balance of substrate oxidation rates. Methods: Eleven male participants performed an incremental exercise test to exhaustion on a cycle ergometer to estimate AT and RCP. Subsequently, we conducted three 30 minute constant load exercise tests at AT (WAT), RCP (WRCP) and 25% below AT (W<AT) in a randomised order. Pulmonary gas exchange parameters measured breath-by-breath. We estimated substrate oxidation rate by using Frayn equations. Results: We found that AT and RCP occurred at a mean intensity of 60% (range between 53-64% of VO2peak) and 72% of VO2peak (range between 66-76% of VO2peak) respectively. Fat oxidation was found to be 0.221±0.01 g/min at W<AT and this significantly increased to 0.340±0.01 g/min at WAT and 0.326±0.03 g/min at WRCP (p<0.05). Conclusion: We found that carbohydrate oxidation was 1.621±0.03 g/min (W<AT), 1.961±0.02 g/min (WAT) and 2.417±0.1 g/min (WRCP) (p<0.05). AT and RCP provides optimal metabolic strain to all participant and stimulate more fat oxidations. Thus clinicians should consider using exercise intensity at AT and RCP to achieve the rate of highest fat oxidation.